Aplikasi Teknologi Pembuatan dan Pengemasan Abon Ikan Nila Dalam Upaya Peningkatan Pendapatan DI Desa Batu Radden - Meiwinda, Eka Rizki; Lucyana, Lucyana; Destiarini, Destiarini; Rahman, Abdul; Azwar, Azwar (Jurnal Gotong Royong, 2024)
The potential of the tilapia (Oreochromis niloticus) fishery as one of the village's leading potentials needs to receive serious attention and development, and be sustainable so that it can produce quality products, if the village community's economy is to be strengthened. To be able to produce processed products made from tilapia fish that can compete in the market, professional business management is needed. This can be realized if the village tilapia fish commodity is run by quality human resources considering that this commodity is vulnerable in terms of quality and marketing. So far, tilapia fish in Batu Raden Village are mostly marketed in whole form without any further processing for restaurant and household consumption. Tilapia fish is mostly marketed in whole form without any further processing for restaurant and household consumption. Efforts to increase the use of tilapia as a raw material for processing ready-to-consume food products such as shredded meat have not been carried out much. Tilapia fish floss processing is one of the efforts to diversify shredded processing by utilizing the availability of raw materials and material characteristics suitable for processing floss